Proceedings of the ICTs for Improving Patients Rehabilitation Research Techniques 2013
DOI: 10.4108/icst.pervasivehealth.2013.252089
|View full text |Cite
|
Sign up to set email alerts
|

Make Me Move at Work! An Ambient Light Display to Increase Physical Activity

Abstract: Physical inactivity has become a normal condition for many people today, and in the long run accounts for 1 out of 10 deaths worldwide. Long sitting periods have been shown to increase the risk of diabetes and cardiovascular disease. In this paper we propose MoveLamp, a system which helps to integrate physical activity into a person's workplace. An ambient light display in the office indicates a person's recent physical activity. While sitting at the desk, typically in front of a computer, the light display he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 13 publications
(13 reference statements)
0
17
0
Order By: Relevance
“…Haller and colleagues [95] connected a posture sensing chair to 3 different types of media for delivering prompts (onscreen graphic feedback, tactile feedback from the chair itself, and physical feedback delivered by a plastic plant that became droopy to represent bad posture of the user); the result was in favor of the physical feedback, as it required the shortest time to return to the main task after the prompted activity and was rated by users as least disturbing. Along the same line of reasoning, several design studies assessed the technological feasibility, ease of understanding, usability, and likeability of ambient displays, such as programmable sculptures that changed shape [56,91], or ambient lights that altered color [94,96] to reflect users’ sedentary time and remind the user to take breaks. Nonetheless, although all the researchers suggested the need for longer-term experiments to establish the viability of their design approaches, no published follow-up studies were found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Haller and colleagues [95] connected a posture sensing chair to 3 different types of media for delivering prompts (onscreen graphic feedback, tactile feedback from the chair itself, and physical feedback delivered by a plastic plant that became droopy to represent bad posture of the user); the result was in favor of the physical feedback, as it required the shortest time to return to the main task after the prompted activity and was rated by users as least disturbing. Along the same line of reasoning, several design studies assessed the technological feasibility, ease of understanding, usability, and likeability of ambient displays, such as programmable sculptures that changed shape [56,91], or ambient lights that altered color [94,96] to reflect users’ sedentary time and remind the user to take breaks. Nonetheless, although all the researchers suggested the need for longer-term experiments to establish the viability of their design approaches, no published follow-up studies were found.…”
Section: Resultsmentioning
confidence: 99%
“…Not to mention easier integration of multiple data sources to make interventions more relevant to the context, CD greatly expands the range of interfaces and media that can be used to deliver SPs to users. We identified exploratory work on developing and piloting ambient displays to deliver break reminders subtly [72,94,96]. The technological advancements in the field of Tangible, Embedded, and Embodied Interactions presents new promise for this line of research, as mechanically controlled objects have been created [56,95] or designed [88,91] as a creative and pleasant way to persuade users into taking breaks and caring for their own health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The system "MoveLamp" from Fortmann et al [8] investigated whether ambient light notification can motivate users to be more physically active. It consisted of an ambient lighting system, which indicated the amount of activity of a user by the color and brightness from green to red.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research also hints at the potential of using ambient technologies for a persuasive purpose [33], for instance at the workplace by nudging employees to take a break (Breakaway by Jafarinaimi et al [22]) or to use the stairs rather than the elevator (Light installations by Rogers et al [33]). Other Figure 1: Yamin (a) and Apphia (b), two ambient desktop devices that visualize computer-activity notable design examples using ambient displays to nudge office workers into moving more are Movelamp [15], which indicates the employee's recent activity level, Lightsit [31] which visualizes unhealthy sitting behavior or posture, or the Healthbar [29] which helps users break their sitting behavior. These examples use and embody several forms of physical activity data, yet none relate physical activity to computer activity data.…”
Section: Introduction and Related Workmentioning
confidence: 99%